Calculation Model of Shear Capacity of Multiple Composite Core Column Joints Based on Softened Tension-Compression Bar Model - Xu Wentao; Yang Chengyu (Advances in Civil Engineering)
This paper aims to study the seismic performance of multiple composite core column joints. The influence of the stress mechanism, axial compression ratio, and shear span ratio on the failure mode, hysteretic performance, and shear capacity of the multiple composite core column joints was studied through the low-reversed cyclic loading tests of three specially designed and manufactured multiple composite core column joints. The angle ratio method is used to calculate the effective area of the vertical tie bar, and based on the mechanism of the softening tension-compression bar, the formula for calculating the shear capacity of the joint with multiple composite core column is established. In addition, it is also verified by the test data in this paper. The experimental results show that when the axial compression ratio increases from 0.26 to 0.45, the number and width of cracks at the beam end decrease. When the shear span ratio increases from 1.67 to 2.22, the number and width of cracks at the joint beam end increase. The average value and standard deviation of the ratio between the measured value and the calculated value of the shear capacity are 0.97 and 0.16, indicating that the proposed calculation method has a high agreement with the actual value and strong engineering application.